2014
DOI: 10.1098/rsif.2014.0858
|View full text |Cite
|
Sign up to set email alerts
|

Which muscles compromise human locomotor performance with age?

Abstract: Ageing leads to a progressive decline in human locomotor performance. However, it is not known whether this decline results from reduced joint moment and power generation of all lower limb muscle groups or just some of them. To further our understanding of age-related locomotor decline, we compare the amounts of joint moments and powers generated by lower limb muscles during walking (self-selected), running (4 m s 21) and sprinting (maximal speed) among young, middle-aged and old adults. We find that age-relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
69
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 48 publications
6
69
2
1
Order By: Relevance
“…Reduced ankle plantarflexion peak power in the late push-off phase of walking is a consistent finding in both healthy and mobility limited older compared to young adults (10, 23,30), and it seems that impairments in plantarflexor force and power generation contribute to a reduction in preferred walking speed in older adults (29). Tendinous tissues (tendon and aponeurosis, TT) elasticity greatly affects muscle function of the main plantarflexor, triceps surae, due to a large tendon to muscle fiber length ratio (41).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Reduced ankle plantarflexion peak power in the late push-off phase of walking is a consistent finding in both healthy and mobility limited older compared to young adults (10, 23,30), and it seems that impairments in plantarflexor force and power generation contribute to a reduction in preferred walking speed in older adults (29). Tendinous tissues (tendon and aponeurosis, TT) elasticity greatly affects muscle function of the main plantarflexor, triceps surae, due to a large tendon to muscle fiber length ratio (41).…”
Section: Introductionmentioning
confidence: 92%
“…Thus, improvement in triceps surae contractile conditions for force generation and consequential decrease in muscle activation to maintain required level of force generation may affect total energy cost of walking and hence drive the selection of slower walking speeds in older adults. In addition, it has been shown that older adults compensate for reduced plantarflexor power and work output during push-off by increasing the use of hip extensors in early stance (10), which may operate with greater reserve capacity (23). However, this distal to proximal shift in muscular strategy, where power generation of plantarflexors that can utilize a catapult action due to a long Achilles tendon (21) is replaced by power generation from an MTU with a short tendon, may increase energy cost of walking due to unfavorable muscle shortening velocities of the muscles providing the positive power (37).…”
Section: Discussionmentioning
confidence: 99%
“…PLANTARFLEXOR PERFORMANCE (i.e., net ankle joint kinetics) during the push-off phase of walking decreases precipitously in old age (6,7,17,21,38). This biomechanical change is often implicated in and may precede the age-related slowing of preferred walking speed, which in turn negatively affects old adults' health and independence (13,31).…”
mentioning
confidence: 97%
“…Our findings: 1) demonstrate a potential role for nonuniform AT deformations in governing gastrocnemius and soleus muscle-tendon function and 2) allude to altered tendon behavior that may contribute to the age-related reduction in plantarflexor performance during walking. ultrasound; gait; triceps surae; kinetics; elderly PLANTARFLEXOR PERFORMANCE (i.e., net ankle joint kinetics) during the push-off phase of walking decreases precipitously in old age (6,7,17,21,38). This biomechanical change is often implicated in and may precede the age-related slowing of preferred walking speed, which in turn negatively affects old adults' health and independence (13, 31).…”
mentioning
confidence: 97%
“…It seems plausi- ble that the accuracy of the current method is sufficient for discriminating between normal and abnormal peak vertical GRF values of recreational runners. As an example, GRF peak values of young, middle-aged, and old athletes were measured and compared in [15]. By calculating the 95th percentiles of the values for each age category, we obtained estimates of the thresholds for abnormal peak forces from these data sets.…”
Section: Discussionmentioning
confidence: 99%